The influence of host country factors on firms' entry mode choice: a cross comparative case study of Pernod Ricard entry strategies in USA and China. - Fernandez, Eva (2012)
The main aim of this study is to provide a deeper understanding of the influence of host country factors on the entry mode choice of firm. Research questions focusing on how these factors influence entry strategies and why one firm may use different entry strategies depending on the target market are investigated. Based on the literature review, a set of four influential host country factors and corresponding propositions is developed. Then, in order to obtain comprehensive findings a cross comparative case study is selected, which analyses the entry mode strategies of one firm, Pernod Ricard, in two different host countries, namely Case 1: USA, entered through an acquisition, and Case 2: China, entered through a JV. Following, the empirical data are collected in relation to the four characteristics identified. Subsequently, the set of propositions is tested for each case individually; afterwards the two cases are confronted in a cross case comparison The findings of the case study highlight that the choice of the optimal entry mode depends on the firm’s priorities in each specific situation and involves tradeoffs between the different influential host country dimensions.